From Synthesis to Biological Impact of Pd (II) Complexes: Synthesis, Characterization, and Antimicrobial and Scavenging Activity. (16th March 2016) - Sharma, Nitin Kumar; Ameta, Rakesh Kumar; Singh, Man
Abstract : The Pd (II) complexes with a series of halosubstituted benzylamine ligands (BLs) have been synthesized and characterized with different spectroscopic technique such as FTIR, UV/Vis, LCMS, 1 H, and 13 C NMR. Their molecular sustainability in different solvents such as DMSO, DMSO : H2 O, and DMSO : PBS at physiological condition (pH 7.2) was determined by UV/Vis spectrophotometer. The in vitro antibacterial and antifungal activities of the complexes were investigated against Gram-positive and Gram-negative microbes and two different fungi indicated their significant biological potential. Additionally, their antioxidant activity has been analyzed with DPPH free radical through spectrophotometric method and the result inferred them as an antioxidant. The stronger antibacterial and antioxidant activities of the synthesized complexes suggested them as a stronger antimicrobial agent. Our study advances the biological importance of palladium (II) amine complexes in the field of antimicrobial and antioxidant activities.